Refinements of Bounds for Neuman Means. (17th March 2014) - Chu, Yu-Ming; Qian, Wei-Mao
Abstract : We present the sharp bounds for the Neuman means S H A, S A H, S C A and S A C in terms of the arithmetic, harmonic, and contraharmonic means. Our results are the refinements or improvements of the results given by Neuman.